Case Report: Opposite Tumoral and Hormonal Responses to Low-dose Pasireotide in Cushing’s Disease - Serban, Andreea L.; Zampetti, Benedetta; Saladino, Andrea; Favero, Vittoria; Chiodini, Iacopo; Cozzi, Renato (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Background: Pasireotide is a multireceptor somatostatin analogue approved for the treatment of patients with Cushing's disease (CD) who are ineligible or poor candidates for pituitary surgery. Here we present a patient with severe recurrent CD who was treated with pasiretide and showed opposite results between hormonal levels and pituitary tumour size. Case Presentation: A 54-year-old woman was diagnosed with CD, a first surgical transsphenoidal procedure was performed at the time of diagnosis, and the disease recurred seven years later. She underwent a second transsphenoidal surgery, but despite apparent complete removal of the adenoma, the hypercortisolism worsened. Magnetic resonance imaging showed a tiny remnant of the adenoma adjacent to the cavernous sinus, and ketoconazole was started at a dose of 800 mg/day. Due to the persistence of pathological urinary free cortisol levels, 600 μg bid pasireotide was added. The combination therapy induced first normalisation of urinary free cortisol and later hypoadrenalism, so that ketoconazole was discontinued and pasireotide was maintained. A marked clinical improvement was achieved with pasireotide. Adrenal insufficiency persisted despite progressive tapering of the pasireotide dose to 150 mg once daily. Pituitary magnetic resonance imaging performed at 12 and 24 months during low-dose pasireotide treatment showed a few millimetres increase of the remnant. Conclusions: This report suggests that CD Pas induces an opposite effect between hormonal profile and increase of pituitary tumor size. This peculiar phenomenon may be a consequence of the unusually low doses of pasireotide needed to control hormonal hypersecretion.
Keywords: pasireotide